Immunosuppressive Drug Levels in Liver Transplant Recipients: Impact in Decision Making - Kourkoumpetis, Themistoklis; Levitsky, Josh (Seminars in Liver Disease, 2019)
To prevent rejection, liver transplant providers largely base their management decisions on their clinical impression and pharmacokinetics. Clinical impression relies on assessing graft function, liver enzymes, and biopsy. High immunosuppressive drug levels, although minimizing rejection, are related to significant side effects such as nephrotoxicity and metabolic syndrome, contributing to long-term morbidity and mortality. Similarly, levels that are lower than necessary can decrease the rate of side effects with a potential toll on rejection and graft survival. Herein, the authors present an update on immunosuppressive drug level monitoring and manipulation strategies according to different scenarios and time from transplant. They also provide a brief overview of next level immunosuppression monitoring strategies that aim to properly balance rejection rates with drug side effect profiles.
Keywords: immunosuppression; liver transplant; drug level monitoring; immune monitoring